Prion protein as a mediator of synaptic transmission - Steinert, Joern R (Commun Integr Biol, 2015)
Neurodegenerative disorders are characterized by synaptic and neuronal dysfunction which precedes general neuronal loss and subsequent cognitive or behavioral anomalies. Although the exact early cellular signaling mechanisms involved in neurodegenerative diseases are largely unknown, a view is emerging that compromised synaptic function may underlie the initial steps in disease progression. Much recent research has been aimed at understanding these early underlying processes leading to dysfunctional synaptic signaling, as this knowledge could identify putative sites of interventions, which could potentially slow progression and delay onset of disease. We have recently reported that synaptic function in a Drosophila melanogaster model can be modulated by the presence of native mouse prion protein and this modulation is negatively affected by a mutation within the protein which is associated with the Gerstmann-Sträussler-Scheinker syndrome, a human form of prion disease. Indeed, wild-type prion protein facilitates synaptic release, whereas the mutated form induced diminished phenotypes. It is believed that together with the gain-of-function of neurotoxic misfolded prion signaling, the lack of prion protein contributes to the pathology in prion diseases. Therefore, our study investigated a potential endogenous role of prion protein in synaptic signaling, the lack of which could resemble a lack-of-function phenotype in prion disease.